2018
DOI: 10.1016/j.ram.2017.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Passive immunity to control Bovine coronavirus diarrhea in a dairy herd in Argentina

Abstract: Bovine coronavirus (BCoV) is a viral enteric pathogen associated with calf diarrhea worldwide being, in Argentina, mostly detected in dairy husbandry systems. The aim of the present work was to study if maternal IgG1 antibodies (Abs) to BCoV acquired by colostrum intake modulate the development of BCoV infection in calves reared in a dairy farm in Argentina. Thirty Holstein calves were monitored during their first 60 days of age. Animals were classified into two groups depending on their initial BCoV IgG1 Ab t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 28 publications
1
24
0
2
Order By: Relevance
“…Was determined, and failures in the quantity and quality of colostrum supplied to neonates have been related to an increase in the occurrence of cryptosporidiosis. Bok et al (2018) showed that calves that had received a satisfactory absorption of colostrum from calves vaccinated against bovine coronavirus (BcoV) had less percent of The occurrence of diseases… soroconversion to BcoV when contrasted to calves that had not received a satisfactory passive immune transfer, indicating that calves without FPIT are more protected against viral infection. The same results were observed by Foster et al (2019) who also demonstrated that calves receiving colostrum from cows vaccinated against Salmonella sp.…”
Section: Discussionmentioning
confidence: 99%
“…Was determined, and failures in the quantity and quality of colostrum supplied to neonates have been related to an increase in the occurrence of cryptosporidiosis. Bok et al (2018) showed that calves that had received a satisfactory absorption of colostrum from calves vaccinated against bovine coronavirus (BcoV) had less percent of The occurrence of diseases… soroconversion to BcoV when contrasted to calves that had not received a satisfactory passive immune transfer, indicating that calves without FPIT are more protected against viral infection. The same results were observed by Foster et al (2019) who also demonstrated that calves receiving colostrum from cows vaccinated against Salmonella sp.…”
Section: Discussionmentioning
confidence: 99%
“…Rotavirus is usually associated with Coronavirus, and both agents are one of the main enteropathogens responsible for neonatal diarrhea syndrome in calves (Coura et al 2015;Hayashi et al 2017;Almeida et al 2018;Bok et al 2018;Fritzen et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, colostrum prevented influenza infection in healthy volunteers at a rate comparable to influenza vaccination (36). Supplementation of IgG1 antibodies from colostrum against bovine coronavirus (BCV) prevented calves from developing viral infections when compared to those treated with low titers of IgG1, showing that IgG1 antibodies from colostrum are crucial for protection against BCV infection (37). Orally-administered egg yolk and colostrum powders from hens and cows vaccinated with inactivated BCV protected calves from coronavirus infection-induced diarrhea in neonates (38).…”
Section: Application Of Igg-derived Hyperimmune Colostrum For Human Hmentioning
confidence: 99%